Financial optimization planning at Mitha Pre-Marriage Healthcare and Aesthetic Clinic - Wulandari, Hesti; Iskandar, Muhammad Dhafi; Indradewa, Rian; Kustiawan, Unggul (Institute of Computer Science (IOCS), 2024)
This study aims to investigate and design financial optimization planning strategies at KLINIK MITHA Pre-Marriage Healthcare and Aesthetic. Healthcare and aesthetic clinics, such as KLINIK MITHA, have an important role in providing quality healthcare and aesthetic treatments to the community. Therefore, effective financial management is key to support their growth and operational continuity. The research method we applied in this study involved a thorough analysis of the clinic's financial structure. We focused on the management of financial resources, which includes aspects of cash management, proper budget allocation, as well as smart investment strategies. We analyzed KLINIK MITHA's financial data over the past few years quantitatively and qualitatively to understand their dynamics and challenges. The results of this study show that effective financial optimization planning is crucial in the context of health and aesthetic clinics. Efficient cash management ensures clinics can meet their operational needs and remain sustainable. Proper budget allocation helps maximize the use of financial resources, while smart investment strategies can provide significant returns on investment. The conclusions of this study strongly emphasize the importance of careful financial planning in achieving operational success and long-term growth in the healthcare and aesthetic services sector. Our findings provide valuable insights for the management of similar clinics that are looking for ways to improve their financial efficiency and achieve sustainable business goals. This research can provide a solid foundation for better financial planning strategies in the future.